Sugar Palm Fruits (Arenga pinnata) as Potential Analgesics and Anti-Inflammatory Agent - Evi Sovia; Dian Anggraeny (Cell and BioPharmaceutical Institute, 2019)
Background: Sugar palm fruit (Arenga pinnata) is used for osteoarthritis empirically. It also has antioxidant activity and showed inhibition to lipoxygenase activity. The study about analgesic and anti-inflammatory activities of sugar palm fruit is still limited, this study was initiated to explore analgesic and anti-inflammatory effects of sugar palm fruit ethanol extract (SFEE).Materials and Methods: Acetic acid induced writhing was performed for screening analgesic activity, meanwhile antiinflammatory activity was tested against rat paw edema. Acute toxicity and phytochemical screening were also investigated.Results: The results of phytochemical screening revealed that flavonoids, alkaloids and quinones were present in SFEE. SFEE 50 and 100 mg/kg have analgesic effect and show the anti-oedematogenic effect against paw edema induced by carrageenan. SFEE could significantly decrease the neutrophils numbers as compared to the carrageenan-treated group. Neutrophil activation has been shown to contribute to tissue inflammation and damage.Conclusion: SFEE have analgetic and anti-inflammatory activity.Keywords: Arenga pinnata, analgesic, anti-inflammatory, acute toxicity